The predictive value of self-compassion for psychological adjustment in left ventricular assist device patients: an observational study - Morgenroth, Olaf; Petersen, Lars-Eric; Frey, Norbert; Reinecke, Alexander (ESC heart failure, 2022)
Heart failure, LVAD, anxiety, depression, self-compassion, functional health status